Functional connectivity and topology in patients with restless legs syndrome: a case–control resting‐state functional magnetic resonance imaging study. (5th November 2020) - Tuovinen, N.; Stefani, A.; Mitterling, T.; Heidbreder, A.; Frauscher, B.; Gizewski, E. R.; Poewe, W.; Högl, B.; Scherfler, C.
Abstract : Background and purpose: Functional connectivity studies revealed alterations within thalamic, salience, and default mode networks in restless legs syndrome patients. Methods: Eighty‐two patients with restless legs syndrome (untreated, n  = 30; on dopaminergic medication, n  = 42; on alpha‐2‐delta ligands as mono‐ or polytherapy combined with dopaminergic medication, n  = 10), and 82 individually age‐ and gender‐matched healthy controls were studied with resting‐state functional magnetic resonance imaging. Connectivity of 12 resting‐state networks was investigated with independent component analysis, and network topology was studied with graph methods among 410 brain regions. Results: Patients with restless legs syndrome showed significantly higher connectivity within salience ( p  = 0.029), executive ( p  = 0.001), and cerebellar ( p  = 0.041) networks, as well as significantly lower ( p  < 0.05) cerebello‐frontal communication compared to controls. In addition, they had a significantly higher ( p  < 0.05) clustering coefficient and local efficiency in motor and frontal regions; lower clustering coefficient in the central sulcus; and lower local efficiency in the central opercular cortex, temporal, parieto‐occipital, cuneus, and occipital regions compared to controls. Untreated patients had significantly lower ( p  < 0.05) cerebello‐parietal communication compared to healthy controls. Connectivity between the thalamus and frontal regions was significantly increased ( p  < 0.05) in patients on dopaminergic medication compared to untreated patients and controls. Conclusions: Networks with higher intranetwork connectivity (i.e., salience, executive, cerebellar) and lower cerebello‐frontal connectivity in the restless legs syndrome patients, as well as lower cerebello‐parietal connectivity in untreated patients, correspond to regions associated with attention, response inhibitory control, and processing of sensory information. Intact cerebello‐parietal communication and increased thalamic connectivity to the prefrontal regions in patients on dopaminergic medication suggests a treatment effect on thalamus. Abstract : This resting‐state functional magnetic resonance imaging study applied graph methods, which revealed dopaminergic‐related alterations in a broad array of brain networks in restless legs syndrome (RLS) patients. In particular, lower cerebello‐parietal connectivity was present in untreated RLS, but not in medicated patients. RLS patients treated solely with dopaminergic medication presented with higher thalamo‐frontal connectivity compared to untreated patients.